FAKTOR-FAKTOR YANG MEMPENGARUHI MANAJEMEN ASET TETAP MILIK PEMERINTAH KABUPATEN KOTA DI SUMATERA BARAT - Hayati1, Miftahul; Ramayani,, Citra; Areva, Desi (Pendidikan Ekonomi, 2014)
ABSTRACT This study aims to determine : 1 ) the extent to which affect asset inventory asset management . 2 ) the extent to which the legal audit affect asset management . 3 ) the extent to which the valuation of assets affect asset management . 4 ) the extent to which asset optimization affects asset management . 5 ) the extent to which the supervision and control of assets affect asset management 6 ) the extent to which asset inventory , legal audit , valuation of assets , optimization , monitoring and control of assets affect asset management . The method used descriptive quantitative methods . Its population DPPKAD office employees especially the regional assets and purposive sampling techniques amounted to 32 people . Data were collected through questionnaires . Data analysis techniques of multiple linear regression . Results of the study : 1 ) a significant difference between the asset inventory asset management . This means that if the asset inventory increased by 1 % then the regression coefficient increased by 0.111 % . 2 ) a significant difference between Legal audit of asset management . That is legal if the audit increased by 1 % then the regression coefficient increased by 0,621 % . 3 ) a significant difference between the valuation of assets to asset management . This means that if the valuation of assets increased by 1 % then the regression coefficient increased by 0.329 % . 4 ) a significant difference between the optimization of asset management . This means that if the asset optimization increases 1 % then the regression coefficient increased by 0.167 % . 5 ) a significant difference between supervision and control of asset management . This means that if the supervision and control increased by 1 % then the regression coefficient increased by 0.300 . Upshot asset inventory , legal audits , asset valuation , asset optimization , monitoring and control significantly influence the management of fixed assets in the City District Government of West Sumatra.